1998
DOI: 10.1101/gad.12.9.1278
|View full text |Cite
|
Sign up to set email alerts
|

The yeast Ada complex mediates the ligand-dependent activation function AF-2 of retinoid X and estrogen receptors

Abstract: Nuclear receptors (NRs) represent a large family of ligand-inducible transcriptional regulators that control complex developmental and homeostatic events in vertebrates by binding as homodimers or heterodimers to cognate DNA response elements present in target genes. NRs display a modular structure, with five to six distinct regions (denoted A-E/F; see Fig. 1A). The amino-terminal A/B region contains an autonomous activation function (AF-1), the highly conserved region C belongs to the DNA-binding domain (DBD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 57 publications
2
50
0
Order By: Relevance
“…Previous genetic studies of mammalian NRs expressed in the yeast have indicated a coactivator role of the evolutionarily conserved ADA complex as a coactivator of NR-mediated gene expression (17,18), a possibility directly supported by our recent demonstration of a coactivator role for hADA3, a component of the mammalian ADA complex, in RXR function (19). Given that these studies relied solely on hADA3 overexpression, and given the existence of a recent study reporting the inability of mouse ADA3 to interact with estrogen receptor (21), we undertook a systematic examination of the mammalian ADA3 interaction with ER and the functional role of this interaction in the context of ectopic as well as endogenous ADA3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous genetic studies of mammalian NRs expressed in the yeast have indicated a coactivator role of the evolutionarily conserved ADA complex as a coactivator of NR-mediated gene expression (17,18), a possibility directly supported by our recent demonstration of a coactivator role for hADA3, a component of the mammalian ADA complex, in RXR function (19). Given that these studies relied solely on hADA3 overexpression, and given the existence of a recent study reporting the inability of mouse ADA3 to interact with estrogen receptor (21), we undertook a systematic examination of the mammalian ADA3 interaction with ER and the functional role of this interaction in the context of ectopic as well as endogenous ADA3.…”
Section: Discussionmentioning
confidence: 99%
“…NRs when these were expressed in yeast (17,18). Furthermore, we have recently shown that hADA3 binds to and functions as a coactivator for RXR␣ (19).…”
Section: Both Hada3 and Mada3 Interact Directly With Er␣ And Er␤-genementioning
confidence: 99%
See 2 more Smart Citations
“…To overexpress GCN5, the hGCN5-S-containing cDNA was PCR-amplified from the pcDNA3-hsGCN5 plasmid (14) and inserted in the XhoIBamHI sites of the pET15bEpB10 expression vector (18). Doubletagged hPCAF was expressed using baculovirus in Sf9 cells and purified in the presence of 1 M acetyl-CoA first on a Ni 2ϩ column, then by an anti-FLAG immunoprecipitation (Sigma) and peptide elution.…”
Section: Methodsmentioning
confidence: 99%